A capacidade participacionista dos conselhos municipais de Curitiba sob a abordagem da governança societal: um estudo multicaso - Barddal, Fabiana Marissa Etzel (2018)
The purpose of this research was to analyze the configuration of civil society participation in the management councils of Curitiba, classified as social councils, based on the Societal Governance approach. In this perspective, a proposal of public management based on participatory democracy and social control, called Societal Governance, was presented. This capacity was analyzed through data available in the creation legislation, the internal regulations and the minutes of the plenary meetings of the social councils, which were collected on the website of the Municipal Councils of Curitiba. The methodology of this study is characterized, from the point of view of nature, as applied research; from the point of view of the objectives, as descriptive and explanatory; according to the problem approach is classified as a qualitative analysis methodology. As for the technical procedures, the research is presented as a case study - multi-site, with bibliographic and documentary research (secondary sources), and content analysis. The inductive method was used, from the observation of the cases, and the results allowed inferences in two levels: municipal and council. At the municipal level, there is a guarantee of popular participation in public power decisions, fostering the creation and functioning of institutions of participatory democracy, and Curitiba presents an incentive profile for deliberative democracy, under a pluralist approach advocated by Societal Governance. In the council level, the analysis of the Municipal Councils of School Feeding, Sports and Health under the Societal Governance approach identified that the figures presented and related to the participation of civil society still do not fit the one recommended by the approach, since the direct participation of civil society actors and external to the council is virtually non-existent. The research also identified that, although present in the city of Curitiba, the institutional-administrative and sociopolitical dimensions need to happen with greater emphasis. In this way, the functioning of the councils is still far from ideal, from the point of view of laws, transparency or Societal Governance.